Integrating Official And Traditional Flood Hazard Management In Malaysia. - Chan, Ngai Weng; Zakaria, Nor Azazi; Ghani, Aminuddin Ab; Tan, Yean Lian (2004)
Malaysia represents one of the "Tiger Economies" of Asia that is rapidly developing, industrialising, and urbanising. However, like all other Asian economies, the country is plagued by seasonal environmental hazards (mostly floods) that significantly reduce its GDP and deplete its annual budget on development.